Bank Liquidity and Stability in an Overlapping Generations Model - Qi, Jianping (Review of Financial Studies, 1994)
In an infinitely repeated version of the Diamond and Dybvig (1983) model, intergenerational transfers enable a bank to achieve interest rate smoothing and to provide depositors with liquidity insurance without Diamond and Dybvig's assumption of no side trades. The bank is subject to runs that may result from either excessive withdrawals or the lack of new deposits. The latter cause, which cannot occur in Diamond and Dybvig's one-generation model, implies that suspension of convertibility may not prevent bank runs. Government intervention may be necessary to maintain bank stability. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.